RELATIONSHIP BETWEEN DIET AND BLOOD SUGAR LEVELS DIABETES MELLITUS TYPE 2 PATIENTS - Karma, Taufiq; Zulmarhamah, Riya (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
Incorrect eating patterns can cause an increase in blood sugar levels in patients with type 2 diabetes mellitus. This study aims to determine the relationship between diet and blood sugar levels in patients with type 2 diabetes mellitus in Lamme Village, Jaya District. The research design used was an analytical survey with a cross sectional study approach. The research location was carried out in Lamme Village, Jaya District. The population of this research is the Lamme Village Community, 41 people. The sample in this study was people suffering from type 2 diabetes mellitus who were selected as samples and were willing to be interviewed. The number of samples required is 41 people. The sampling technique uses purposive sampling technique. The research instruments needed are a questionnaire about the identity and characteristics of the respondent, a 3x24 hour food recall form, when checking blood sugar, food pictures, the SPSS program. The results obtained are that the majority of Lamme Village residents are aged 41-67 years, this age is in the late adult and elderly category, many sufferers of non-communicable diseases such as type 2 DM suffer at this age. The occupational variable itself shows that there are relatively few people with type 2 DM in the sample compared to the history of other diseases. The most variable nutritional status of type 2 DM patients is normal nutritional status.